2015
DOI: 10.1016/j.proenv.2015.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Cumulative Distribution Function (ECDF) Analysis of Thunnus.sp Using ARGO Float Sub-surface Multilayer Temperature Data in Indian Ocean South of Java

Abstract: Spatial distribution of tuna (Thunnus.sp) in Indian Ocean south of Java has been investigated. Tuna was scientifically known as thermo-conformer species, thus their distribution were strongly influenced by sub-surface temperature. Tuna species in this study comprise of bigeye tuna (Thunnus obesus), albacore tuna (Thunnus alalunga), yellowfin tuna (Thunnus albacares) and southern bluefin tuna (Thunnus maccoyii). The study was conducted in the area between 100 o E -127 o E and 7 o S -20 o S during 2013 covering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
11
0
4
Order By: Relevance
“…To describe the relationship between oceanographic conditions of SST, Chl-a and fish CPUE, empirical cumulative distribution function (ECDF) analysis was used. The ECDF functions (Sukresno et al 2015) can be mathematically represent as follows:…”
Section: Methodsmentioning
confidence: 99%
“…To describe the relationship between oceanographic conditions of SST, Chl-a and fish CPUE, empirical cumulative distribution function (ECDF) analysis was used. The ECDF functions (Sukresno et al 2015) can be mathematically represent as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Qu et al (2005), stated that sub-surface temperature in the Indian Ocean was influenced by monsoon. In addition temporal distribution of sub-surface temperature in Indian Ocean part South of Java was warmer in northwest monsoon than in southeast monsoon (Sukresno et al, 2014;Hartoko, 2010). The current study showed that ALB catches varied in the temperature range with the highest frequency at 24.0-24.9 0 C. Different result from Sukresno et al (2014), in the same region concluded ALB were found with optimum temperature between 17 -21 0 C, where ALB avoids waters below 14 ºC (Arrizabalaga et al, 2015).…”
Section: Gam Achiementmentioning
confidence: 99%
“…In addition temporal distribution of sub-surface temperature in Indian Ocean part South of Java was warmer in northwest monsoon than in southeast monsoon (Sukresno et al, 2014;Hartoko, 2010). The current study showed that ALB catches varied in the temperature range with the highest frequency at 24.0-24.9 0 C. Different result from Sukresno et al (2014), in the same region concluded ALB were found with optimum temperature between 17 -21 0 C, where ALB avoids waters below 14 ºC (Arrizabalaga et al, 2015). Meanwhile Zainuddin et al (2011), in the western North Pacific Ocean indicated that the highest concentrations of ALB were found in water of 18.5 -21.5 ºC and tended to be centered at 20 ºC.…”
Section: Gam Achiementmentioning
confidence: 99%
See 1 more Smart Citation
“…Namun demikian, umumnya hubungan antara kelimpahan sumberdaya perikanan dengan dinamika faktor lingkungannya tidak linear sehingga pendekatan statistik lebih berkembang dan banyak digunakan (Zuur et al, 2009). Sukresno et al, (2015) memprediksi sebaran spasial tuna di Samudera Hindia menggunakan pendekatan statistik polinomial regresi berdasarkan parameter suhu perairan. Dari berbagai pendekatan statistik yang ada, generalized additive model (GAM) lebih banyak digunakan untuk pemodelan habitat suatu jenis ikan karena lebih mampu mengakomodasi hubungan yang tidak linear tersebut (Valavanis et al, 2008).…”
Section: Pendahuluanunclassified